What is the "opposite" of a value? A lexical investigation into the structure of generally undesirable goal content. Issue 3 (28th September 2021) - Wilkowski, Benjamin M.; Williamson, Laverl Z.; Rivera, Emilio; Fetterman, Adam; Meier, Brian P.
Abstract: Objectives: Past taxonomies of goal‐content have focused (either exclusively or predominantly) on generally‐desirable values, and they suggest that some values oppose other values. However, many goals are generally‐undesirable (i.e., the average person is committed to avoiding them), and these "vices" have been under‐studied. This is an important gap because other models suggest that the "opposite" of a value is actually a vice. Methods: To fill this gap, we conducted a lexical investigation. Two large samples (involving 504 undergraduates & 257 online participants) first rated their commitment to approaching or avoiding a large number of goals from the English lexicon. Results: Analyses indicated that vices can be summarized in terms of Elitism, Rebellion, and Disrepute, which appear opposite from Inclusiveness, Tradition, and Prominence values (respectively) in MDS models. In Study 3 (involving 280 undergraduates) and Study 4 (involving 261 online participants), we found that Schwartz values of Universalism, Tradition, and Self‐Enhancement actually appeared opposite from Elitism, Rebellion, and Disrepute (respectively) in MDS models, rather than from other values. Conclusions: This investigation develops an instrument which can distinguish between different vices at a holistic level, and it suggests that they are actually the opposite of select values.